Time-series models for statistical process control (SPC) - Lui, Woei Wen. (2009)
With the objective of reducing process variability, Statistical Process Control (SPC) aims to improve a process by detecting, identifying, and removing special causes of variation. The primary SPC method used to monitor the quality of a given process is the control chart. Based on the classic work of Shewhart, the fundamental assumption used in the construction of the control chart is that the inherent process is independent and identically distributed (iid).